ผลของระดับแรงอัดตามแนวแกนและรูปแบบเหล็กปลอกเดี่ยวที่มีต่อความเหนียวและการสลายพลังงานของเสาคอนกรีตเสริมเหล็ก - จตุพล เทพมังกร (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
In this research, six reinforced concrete cantilever columns with moderate confinement were tested under cyclic lateral loads and moderate axial load levels. Each column specimen was 400 mm by 400 mm in cross section, 1500 mm in height, and reinforced with 3.14% of longitudinal steel ratio. The transverse reinforcement consisted of hoop ties and ACl crossties. Three different hook configurations were considered, viz. 90-deg hooks, 135-deg hooks and 90-deg hooks with hook-clips. The transverse reinforcement provided was about 50% of the confinement steel required by ACl Code in areas of high seismicity, except one speciment whose confinement steel was reduced by half. The test results indicated that and increase in axial load level from 0.30 to 0.37 of the axial compressive strength based on the cylinder strength and gross cross-sectional area caused substantial reductions in the displacement ductility factor and the cumulative energy dissipation. In the case of 135-deg hook ties, the displacement ductilityfactor was reduced by about 4% from 2.7 to 2.6, and the cumulative energy dissipation was reduced by 7%. In the case of 90-deg hook ties with hook-clips, the corresponding reductions were 29% and 46%, respectively. For the same axial load ratio of 0.30, the specimen supplied with 90-deg hook ties and hook-clips sustained a displacement ductility factor of 3.8, which was 2.0 times and 1.4 times of the specimens with conventional 90-deg hook ties and 135-deg hook ties, respectively, while the cumulative energy dissipation was 6.3 times and 2.4 times for the latter specimens, respectively. Based on the effective confinement steel ratio proposed by Lukkunaprasit and Sittipunt which accounts for the effects of axial load levels and tie configurations, the amount of lateral steel for an expected displacement ductility demand was obtained from regression analyses of the experimental results obtained from this research and others. Studies on energy dissipation indexes indicated that the loading history had a pronounced effect on those indexes. For a given specimen, increasing the imposed deformation in each loading step from one yield displacement to twice the value resulted in a significant decrease in the energy dissipation at large values of the effective confinement steel ratio.